Sex differences in intuitive eating and its relationship with body mass index among adults aged 18–40 years in Saudi Arabia: a cross-sectional study - Albajri, Eram; Naseeb, Manal (Frontiers in Nutrition, 2023)
Intuitive eating (IE) is eating without judgment, relying only on physiological hunger and satiety. Sex differences in IE have been reported; however, none of the studies have explicitly examined IE and its relationship with body mass index (BMI) in the Saudi Arabian population. Thus, this study aimed to investigate sex differences in IE and its relationship with BMI in the Saudi population. A cross-sectional online survey of 360 participants (18 years or older) with self-reported weight and height was conducted. IE was measured using the Intuitive Eating Scale-2 (IES-2). Separate multiple linear regression analyses were conducted to determine if total IE and its subscale scores differed across sexes. It was also conducted to assess the relationship between IE and BMI across sexes. Women had higher total IE score, eating for physical rather than emotional reasons (EPR), and body-food choice congruence (BFCC) scores compared to men (p=0.013, p=0.01, p<0.001, respectively). The analysis showed a significant negative association between total IE, BFCC, EPR scores, and BMI in women compared to men (p=0.023, p=0.01, p=0.003, respectively). The data on the sex differences in IE and its subscales and their different association with BMI encourage tailing nutrition-related recommendations in the context of intuitive eating based on sexes. Future studies are needed to explore how intuitive eating functions differently in women compared to men and explore the causal relationship between IE and BMI in this population.